PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP KEPUASAN NASABAH PENGGUNA BNI MOBILE BANKING MELALUI CITRA BANK SEBAGAI VARIABEL INTERVENING - Sri Nawangasari; Nadea Dwirahma Putri (Jurnal Ilmiah Matrik, 2020)
This study aims to determine the effect of e-service quality and e-trust on customer satisfaction of BNI Mobile banking users through the image of the bank as an intervening variable. Data used in this study are primary data, data collection through questionnaires with a total sample of 185 respondents who are "BNI Mobile banking" customers use a purposive sampling technique. Analysis of the data used is descriptive analysis and path analysis. The results showed that: The e-service quality variable directly affected the customer satisfaction variable; The e-trust variable directly influences the customer satisfaction variable; e-service quality variables affect the image of the bank, e-trust variables affect the image of the bank, and the image of the bank affect customer satisfaction. Thus, BNI Bank should continue to improve service quality and trust in the Bank so that customers feel satisfied so that the bank's reputation is better.